2020
DOI: 10.1177/1534735420932648
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of Regional Hyperthermia: Updates From 2010 to 2019

Abstract: The role of hyperthermia (HT) in cancer therapy and palliative care has been discussed for years in the literature. There are plenty of articles that show good feasibility of HT and its efficacy in terms of tumor response and survival improvements. Nevertheless, HT has never gained enough interest among oncologists to become a standard therapy in clinical practice. The main advantage of HT is the enhancement of chemotherapy (CHT), radiotherapy (RT), chemoradiotherapy (CRT), and immunotherapy benefits. This eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 73 publications
(311 reference statements)
0
17
0
Order By: Relevance
“…They state that HT combined with RT or CT should be suggested to all patients "with advanced or recurrent [breast cancer] or at high risk of local recurrence." 1 We think that this statement is too general and "advanced breast cancer" as a recommended indication is too diffuse. We share the authors' view that "HT has never gained enough interest among oncologists to become a standard therapy in clinical practice."…”
Section: Dear Editormentioning
confidence: 99%
See 3 more Smart Citations
“…They state that HT combined with RT or CT should be suggested to all patients "with advanced or recurrent [breast cancer] or at high risk of local recurrence." 1 We think that this statement is too general and "advanced breast cancer" as a recommended indication is too diffuse. We share the authors' view that "HT has never gained enough interest among oncologists to become a standard therapy in clinical practice."…”
Section: Dear Editormentioning
confidence: 99%
“…Toxicity of combined HT/RT is especially important since most patients presenting with LRBC in pre-irradiated sites are treated with palliative intent. Toxicity data presented in Table 4 by Fiorentini et al 1 are neither complete (e.g., Linthorst et al 2 reported in detail HT-related thermal skin damage) nor correct (e.g., Oldenborg et al 3 reported ≥G3, not >G3 toxicity of 24%).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous clinical trials have proven that it is a promising approach to combine hyperthermia treatment (HT) with chemotherapy, enhancing certain anticancer drug's effects. The combination of hyperthermia and radiotherapy makes some cancer cells more sensitive to radiation while other normal cells are kept intact [2]- [4]. Tissue characteristics, tumor site, size, temperature control, duration of treatment, and flow of heat in the tumor tissue play a vital role in the effectiveness of HT [3].…”
Section: Introductionmentioning
confidence: 99%